PENGARUH RENDAM KAKI MENGGUNAKAN AIR HANGAT DENGAN CAMPURAN GARAM DAN SERAI TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI DI UPT PSTW HUSNUL KHOTIMAH - Ari Irawan; Awaludin Awaludin; Osi Draini (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Hypertensive disease in Indonesia has a prevalence of 34.1%. Riau is ranked 23rd with a prevalence of (29.14%) while for Pekanbaru City it is 33%. One of the traditional treatments that can be done to treat hypertension is the provision of foot bath therapy using warm water with a mixture of salt and lemongrass. The purpose of this study was to determine the effect of foot bath therapy using warm water with a mixture of salt and lemongrass on reducing high blood pressure in the elderly. This research design is quantitative using a quasy experiment design with a one group pre-test post test design. The population in this study amounted to 30 people. The sample in this study amounted to 30 people, the sampling technique used the total sampling method. The measuring instrument used is a digital sphygmomanometer. The analysis used used the wilcoxon test. The results obtained the average value of systolic blood pressure before before soaking the feet using warm water with a mixture of salt and lemongrass 149.50 mmHg and after 132.50 mmHg while the average value of diastolic blood pressure before 90.00 mmHg and after 80.50 mmHg obtained a systolic p-value of 0.000 and diastolic 0.000 p-value 0.05. The conclusion of this study is that there is an effect of foot bath therapy using warm water with a mixture of salt and lemongrass on reducing high blood pressure in the elderly at Khusnul khotimah PSTW Pekanbaru. It is hoped that hypertensive elderly people can do foot soaks using warm water with a mixture of salt and lemongrass which is one of the altarnative reducing high blood pressure.Keywords: Hypertension, Warm Water, Salt, Lemongrass